2015
DOI: 10.1176/appi.ps.201400429
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Mortality Rates of Inmates With Mental Illness After a Tobacco-Free Prison Policy

Abstract: This striking correlation of quick and substantial reduction of mortality among individuals with a mental illness in association with the reduction and subsequent ban of smoking suggests that smoking may play a major role in the reduced life span of persons with mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…While evidence from the USA shows that these smoke‐free policies have significantly improved the health of people in prison, these policies have resulted in some unintended consequences. One such example is the diverted use of nicotine replacement therapy (NRT), where prisoners are substituting traditional cigarettes by creating their own cigarettes out of NRT supplied by correctional authorities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While evidence from the USA shows that these smoke‐free policies have significantly improved the health of people in prison, these policies have resulted in some unintended consequences. One such example is the diverted use of nicotine replacement therapy (NRT), where prisoners are substituting traditional cigarettes by creating their own cigarettes out of NRT supplied by correctional authorities.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence from the USA shows that these smoke-free policies have significantly improved the health of people in prison, 3,12 these policies have resulted in some unintended consequences.…”
mentioning
confidence: 99%
“…Two US‐based studies reported significant declines in prisoner deaths following the introduction of correctional smoke‐free policies , providing support for their positive impact on prisoner health. However, one unintended consequence of the policy, reported in some correctional facilities, has been prisoners’ creation of cigarettes using nicotine replacement therapy (NRT) provided by correctional or health authorities to assist with nicotine withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Despite good evidence that smoke-free policies result in health benefits for people in prison,23 24 including significant reductions in smoking-related deaths,7 they do not ensure complete abstinence for all people in prisons. The prevalence of any level of tobacco use in smoke-free prisons has been reported between 20% and 76%,4 however no study has reported this prevalence in an Australian prison.…”
Section: Introductionmentioning
confidence: 99%